Congenital Hypothyroidism: Incidence, Etiology and Laboratory Screening - Liong Boy Kurniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Congenital hypothyroidism is a condition resulting from a deficiency of thyroid hormone in newborns. Congenital hypothyroidism has no specific signs and symptoms at birth. It may lead to severe mental retardation and growth, and developmental disorders. Therefore, it is essential to perform newborn laboratory screening tests for prompt diagnosis and treatment to minimize the sequels. Laboratory screening tests are performed by taking prick blood from the heel of newborn and testing either TSH or T4 or both of them. Currently, the congenital hypothyroidism screening is not mandatory in Indonesia, but some multicentered screening programs have been performed. In Indonesia, a TSH level above 20 µU/mL is used as a cutoff that needs a confirmatory test using serum samples to confirm congenital hypothyroidism diagnosis. Once the diagnosis is established, prompt treatment and laboratory monitoring are needed for a better outcome.